Designer life using synthetic biology. (1st December 2014) - Hessel, Andrew
This article is a starting place for anyone that has not yet been exposed to synthetic biology or the concept of designing living things. It is not an exhaustive review of these areas by any means. It is more of an orientation – a first step into a vast and still almost completely unexplored space. It describes what synthetic biology is, examines some of the trendlines, and peers a short way into the future of this technology. For those that are interested, it also offers some pointers for how to get started.